How to age right and care(fully) at home? A protocol for a multistage comparative study of ageing in place and hospital at home care across three countries - Sturge, Jodi; Nordin, Susanna; Pilosof, Nirit Putievsky; Vogt, Tobias; Janus, Sarah I M; Ludden, Geke; Helder, Ronald; Kylén, Maya; Zimlichman, Eyal; Glazer, Jacob (BMJ open, 2025)
IntroductionAgeing right care(fully) is a transnational research study which explores and maps an understanding of the care pathways between ageing in place and hospital at home policy and practices for older adults in Israel, the Netherlands and Sweden. The countries are suited to be compared where they have growing, ageing populations, a focus on healthcare reform and several policies to reduce the cost of care for older populations. Ageing in place is a government-led policy that is often associated with choice; however, there is a recent debate about whether ageing in place is a universal desire for all older adults. Research shows that the care pathway between the hospital and the home, associated with ageing in place, can impact well-being, especially if the built, social and technological environments do not meet the healthcare needs and preferences of older adults. This is significant as new programmes for digital hospital at home innovations are being developed as part of a global transformation in healthcare systems. The aim of the study is to compare different approaches to ageing in place and hospital at home care in different regions. The multiapproach study explores the demographics, policy structure, decision-making process and the crucial role of the built, social and technological environments along the hospital to home care pathways of older adults.Methods and analysisThe mixed-method, comparative study includes a new multienvironment theoretical contribution explored across a three-phase research method to understand the care pathways of older adults ageing in place receiving hospital at home care. The first phase compares each country’s population and policy structures relating to ageing in place, hospital discharge, home hospitalisation and at-home care for older adults. The second phase maps patient journeys of older adults living in each country through the perspective of the older adult, caregivers and care professionals. The third phase explores the synergies between the knowledge gained through phases 1 and 2—from a policy and a personal level—and mobilises the knowledge into policy recommendations and implementation guidelines.Ethics and disseminationThe comparative study has been approved by the Sheba Medical Centre in Israel (SMC-1330-24), the Ethics Committee of Tel Aviv University (0009216-2), the Humanities and Social Science Ethics Committee at the University of Twente in the Netherlands (240040) and the Swedish Ethical Review Authority (Dnr 2024-07569-01). The results will be shared with end-users, including citizens, carers, healthcare policymakers, planners, architects and designers, through social media, publications, workshops and international conferences. This future-focused research approach will allow stakeholders to rethink and imagine ways that health and care systems can be personalised and responsive to the future needs of older adult populations.